2011
DOI: 10.1007/s00467-011-2044-1
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract infection following kidney transplantation: frequency, risk factors and graft function

Abstract: The aim of this study was to determine the proportion of children who develop urinary tract infection (UTI) after kidney transplantation (KTx) and to identify the factors associated with UTI and its impact on graft function. To this end, we undertook a chart review of children who underwent KTx at Red Cross Children's Hospital between January 2003 and December 2009 and were followed-up for at least 6 months after transplantation. Sixty-two children (53.2% males) were followed-up for a mean (standard deviation)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 21 publications
5
15
1
1
Order By: Relevance
“…Several studies concluded that the presence of lower urinary tract abnormality is a significant risk factor for posttransplant UTI [12,13]. However the prevalence of UTI in LUTD (þ) patients varies widely in the literature due to many factors, such as differences in the definition of UTI, agents chosen for prophylaxis, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies concluded that the presence of lower urinary tract abnormality is a significant risk factor for posttransplant UTI [12,13]. However the prevalence of UTI in LUTD (þ) patients varies widely in the literature due to many factors, such as differences in the definition of UTI, agents chosen for prophylaxis, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, functional bladder disorders do not increase the risk for UTI or the incidence of UTI after transplant, but patients with recurrent UTI have a more rapid decrease in GFR . Obstructive uropathy, pretransplant pyelonephritis, pretransplant vesicoureteral reflux, age <5 years, and congenital anomalies of the kidneys and urinary tract (mainly posterior urethral valves) have been identified as risk factors for post‐transplant UTI . However, at 2‐year follow‐up, no difference could be shown in eGFR between patients with febrile UTI and those without febrile UTI.…”
Section: Discussionmentioning
confidence: 99%
“…Kidney transplantation (KT) is the treatment of choice for end-stage renal disease (ESRD) in children [1] [2]. Despite improvements on immunosuppressive therapy and surgical techniques, infections remain important complications and have been associated with increased morbidity and graft rejection [3] [4].…”
Section: Introductionmentioning
confidence: 99%